Cloning and expression of immunogenic Clostridium botulinum C2I mutant proteins designed from their evolutionary imprints. (August 2019) - Prisilla, A.; Chellapandi, P.
Highlights: We cloned and expressed C2I mutant genes evaluated previously from their evolutionary imprints. C2I mutant proteins exhibited a reduced ADP ribosyltransferase activity with more immunogenic and vaccinogenic characteristics. Recombinant C2I proteins with S197 A and Y298 F suggested as suitable subunit vaccine candidates. Abstract: C2 toxin produced from Clostridium botulinum serotypes C and D has a potential role in many pathophysiological mechanisms in birds and animals. It has encompassed an ADP ribosyltransferase subunit (C2I) and a translocation/binding subunit (C2II). In the present study, we intended to produce C2I mutant proteins as recombinant subunit vaccines by using glutathione-S-transferase-gene fusion system. The mutants of this study were previously evaluated from their evolutionary imprints and suggested as suitable candidates for subunit vaccines. A synthetic C2 gene was inserted in a pGEX-2T vector, cloned and expressed in Escherichia coli BL21 host. The expressed mutant proteins were purified by using glutathione-agarose column and then examined for their ADP ribosyltransferase activity and vaccinogenic characteristics. The pGEX-2T-C2I constructs with Y298F, S347A and S350A substitutions have shown effective transformation efficiencies in E. coli XL10 competent cells but their mutagenesis efficiency was relatively low. Gene expression analysis indicated the rate of gene expression was depended on the fused mutant genes. A high-level expression was achieved for Y298F, S347A and S350A mutant proteins. All purified protein exhibited a molecular mass of 49 kDa. C2I mutant proteins exhibited a reduced ADP ribosyltransferase activity with retained immunogenic and vaccinogenic characteristics compared to the wild-type C2I subunit. The overall analysis of our study suggested the recombinant C2I proteins (S197A and Y298F) are the most promising candidates for the development of subunit vaccine or immunogen for C2 mutants mediated diseases in birds and animals.